Effects of ultrahigh pressure and ultrasound pretreatments on properties of strawberry chips prepared by vacuum-freeze drying. (15th January 2020) - Zhang, Lihui; Liao, Li; Qiao, Yu; Wang, Chao; Shi, Defang; An, Kejing; Hu, Jianzhong
Highlights: Untrahigh pressure combined ultrasound (UHP-US) improved quality of dried strawberry. UHP-US application reduced drying duration and energy consumption. UHP-US pretreatment improved the retention of antioxidative substances andredness. UHP-US pretreatment induced mirostucture alteration and water redistribution. Abstract: The present work investigated the influences of ultrahigh pressure (UHP), ultrasound (US) and their combination (UHP-US) as pretreatments on properties of vacuum-freeze dried strawberry slices. During vacuum-freeze drying, drying duration and total energy consumption of UHP sample, US sample and UHP-US sample was decreased. After the UHP or US pretreatments, a* value (redness), antioxidative substances (total anthocyanin content, total flavonoid content, total phenolic content, diphenyl picrylhydrazyl (DPPH), hydroxyl (–OH) radical-scavenging assay), hardness and cross-section areas of matrix in the dried slices were significantly ( P  < 0.05) increased. Transverse relaxation times and peak area corresponding to free water in the pretreated samples were obviously decreased, indicating lower mobility in the pretreated samples. As compared with UHP or US individually, UHP in combination with US increased those parameters more pronouncedly. Therefore, UHP and US are promising techniques for the vacuum-freeze drying processing of strawberry products.